THE ROLE OF SOCIAL CAPITAL IN MEDIATING THE INFLUENCE OF FINANCIAL TECHNOLOGY, FINANCIAL LITERACY, ON STUDENTS' FINANCIAL INCLUSION - Rima Patricia; Ario Purdianto (Majapahit Journal of Islamic Finance and Management, 2026)
This study was conducted to examine the influence of financial technology and financial literacy on the level of financial inclusion of students by involving social capital as an intervening variable. The study used a quantitative approach with a survey method. The study population was students of Swadaya Gunung Jati University, while the sample was determined through a purposive sampling technique. Data were collected using questionnaires distributed throughout the study period. Analysis of the relationship between variables was conducted using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method using SmartPLS software. The results showed that financial technology plays a significant role in increasing student financial inclusion. Conversely, financial literacy did not show a significant direct effect on financial inclusion. However, financial literacy was shown to have a significant effect on social capital, while financial technology did not significantly influence social capital. Furthermore, social capital did not have a significant effect on financial inclusion and was unable to mediate the effects of financial technology or financial literacy on financial inclusion. This study recommends that increasing student financial inclusion be focused on strengthening accessible and secure digital financial services, supported by ongoing efforts to improve financial literacy.